Analysis of Palm Oil Biomass Utilization and Renewable Energy Innovation on Production Cost Efficiency and Financial Added Value of the Palm Oil Industry in Central Kalimantan - Judijanto, Loso; Arif, Ichwan (West Science Interdisciplinary Studies, 2025)
This study investigates the impact of palm oil biomass utilization and renewable energy innovation on production cost efficiency and the financial added value of the palm oil industry in Central Kalimantan. A quantitative approach was employed, with data collected from 120 respondents using a Likert scale (1–5). The analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The results show that both biomass utilization and renewable energy innovation significantly improve production cost efficiency. In turn, production cost efficiency positively affects financial added value. Renewable energy innovation also has a direct positive effect on financial added value, while biomass utilization affects financial outcomes indirectly through production cost efficiency. These findings highlight the importance of integrating sustainable energy practices and biomass management into palm oil operations to achieve both economic and environmental benefits.